2010
DOI: 10.2337/db10-0326
|View full text |Cite
|
Sign up to set email alerts
|

Naloxone, but Not Valsartan, Preserves Responses to Hypoglycemia After Antecedent Hypoglycemia

Abstract: OBJECTIVEHypoglycemia-associated autonomic failure (HAAF) constitutes one of the main clinical obstacles to optimum treatment of type 1 diabetes. Neurons in the ventromedial hypothalamus are thought to mediate counterregulatory responses to hypoglycemia. We have previously hypothesized that hypoglycemia-induced hypothalamic angiotensin might contribute to HAAF, suggesting that the angiotensin blocker valsartan might prevent HAAF. On the other hand, clinical studies have demonstrated that the opioid receptor bl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
33
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 33 publications
(35 citation statements)
references
References 43 publications
2
33
0
Order By: Relevance
“…While assessing molecular mechanisms mediating the suppression of counterregulation by estradiol, we observed that estradiol inhibited hypothalamic Cpt1a, plausibly contributing to counterregulatory failure by increasing reliance on glycolysis [94]. Similarly we observed that repetitive hypoglycemia also reduced hypothalamic expression of Cpt1a in association with counterregulatory failure [95]. We also confirmed the induction of Cpt1a by fasting in the hypothalamus, but not the cortex [34].…”
Section: Free Fatty Acids Oppose Effects Of Glucose On the Activity Osupporting
confidence: 64%
See 2 more Smart Citations
“…While assessing molecular mechanisms mediating the suppression of counterregulation by estradiol, we observed that estradiol inhibited hypothalamic Cpt1a, plausibly contributing to counterregulatory failure by increasing reliance on glycolysis [94]. Similarly we observed that repetitive hypoglycemia also reduced hypothalamic expression of Cpt1a in association with counterregulatory failure [95]. We also confirmed the induction of Cpt1a by fasting in the hypothalamus, but not the cortex [34].…”
Section: Free Fatty Acids Oppose Effects Of Glucose On the Activity Osupporting
confidence: 64%
“…As suggested above, hypoglycemia produces similar metabolic [31] and molecular [95] effects as produced by fasting [34, 100]. In turn, metabolic responses to fasting require Ppar-alpha [100-103].…”
Section: Free Fatty Acids Oppose Effects Of Glucose On the Activity Omentioning
confidence: 99%
See 1 more Smart Citation
“…A single episode of hypoglycemia induces several Ppar-alpha target genes in the VMH, and the induction of these genes is preferentially lost after antecedent hypoglycemia which impairs counterregulatory responses to hypoglycemia [49]. Furthermore, Ppar-alpha knockout mice exhibit elevated whole-body glucose metabolism that is not reversed by replacing Ppar-alpha in the liver, but is reversed by activating Ppar-alpha in the brain [50].…”
Section: Ppar-alpha and Cbp Determine Vmh Glucose Metabolism And Thementioning
confidence: 99%
“…Opioid receptors are expressed within the VMH and a number of other hypothalamic and thalamic regions where they might conceivably modulate glucose sensing during hypoglycemia (15). However, evidence for a direct role for opioids in the hypothalamus is limited to studies showing reversal of hypoglycemia-induced changes in gene expression (16), and there are as yet no in vivo animal studies that have examined the effect of hypothalamic manipulation of opioid action on perturbations of glucose homeostasis such as hypoglycemia.…”
mentioning
confidence: 99%